SYMBOLISM IN NATHANIEL HAWTHORNE'S THE HOUSE OF THE SEVEN GABLES - Alex Arsyad, Muhammad (2007)
This study elaborates the tragic life of a family caused by bad impact of the past wrongdoing, as depicted in Nathaniel Hawthorne's The House of the Seven Gables using symbolism approach. The aim of this study is to find the core idea as well as message in Nathaniel Hawthorne's The House of the Seven Gables by analyzing the symbols in his novel. This study belongs to qualitative study. In this method, there are two types of data source used by the researcher, namely primary and secondary data sources. The primary data source and the object of the study is the novel The House of the Seven Gables itself, meanwhile the secondary data source are some information about The House of the Seven Gables, the author's biography, some books and articles related to the subject. The researcher collects the data from primary and secondary data sources in a sort of document as evidence. The study uses the library research to collect the data. The collected data are analyzed by means of descriptive analysis. Having analyzing this novel, the writer draws conclusions as follows: first, a literary work involves the response of the author toward the experiences of their life. Second, Nathaniel Hawthorne criticizes that every people's bad action will get punishment and the wrongdoing itself not only will bring bad impact for them but also for the others.